Artificial oocyte activation with ionomycin compared with A23187 among patients at risk of failed or impaired fertilization. Issue 1 (January 2023) - Jia, Lei; Chen, Panyu; Su, Wenlong; He, Shujing; Guo, Yingchun; Zheng, Lei; Fang, Cong; Liang, Xiaoyan
ABSTRACT: Research question: Do fertilization rates differ between intracytoplasmic sperm injection (ICSI) cycles treated with artificial oocyte activation (AOA) using 10 µmol/l ionomycin or commercial A23187 in women at risk of failed or impaired fertilization? Design: This single-centre, 7-year retrospective cohort study included 157 couples with a history of total fertilization failure (TFF, 0%) or low fertilization (<30%) after ICSI, or with severe oligo-astheno-teratozoospermia (OAT) in the male partner. Couples and underwent 171 ICSI–AOA cycles using either 10 µmol/l ionomycin or commercial A23187. The embryological and clinical outcomes were compared. Results: Fertilization rates in the ionomycin group were significantly higher than those in the A23187 group for all three subgroups (TFF, 46.9% versus 28.4%, P = 0.002; low fertilization, 67.7% versus 49.2%, P < 0.001; severe OAT, 66.4% versus 31.6%, P < 0.001). AOA with ionomycin significantly increased the day 3 cleavage rate ( P = 0.009) when compared with A23187 in the low fertilization group, but not in the TFF or severe OAT group (both P > 0.05). The rates of day 3 good-quality embryos, clinical pregnancy, implantation and live birth, and the cumulative live birth, did not differ between the two groups (all P > 0.05). A total of 64 live births resulted in 72 healthy babies born. Conclusions: AOA with 10 µmol/l ionomycin may be more effective than commercial A23187 in improving oocyte activation in patients at risk of failed or impaired fertilization, especially in cases of sperm-related defects.